The Teacher's Work in Classroom: teaching to read and to write - Maria Cecília de Oliveira Micotti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
Currently, the alphabetization as pertaining to school work is a sufficiently complex situation. Education has been criticized, frequently; it is attributed to the student's low performances in reading and writing. The teacher's formation is also questioned by not being adjusted to the educational reality of the country. On the practice, we observe the shock of new pedagogical proposals - principally of the cycling curricular structure and the constructivism - with the practical ones that have been predominated for long time in the education system. The pedagogical proposals interpretations aren't uniforms in teaching work; they vary with the schools and the classrooms. Many times, the constructivism is confused with old methods. As current education is affected by proposals of complex pedagogical changes, the understanding of what occurs with the alphabetization can be facilitated by the distinction between the practices entailed to the diverse theoretical conceptions. The study of the alphabetization didactics can help to the development of this process for allowing identifying the transpositions of the diverse theoretical conceptions to the school work. In this article, we present a general vision of the methodological boardings and the didactics practices that corresponds to them. For this, we revisit the alphabetization methods, the pedagogical proposal elaborated by Paulo Freire for the adults' alphabetization.